ANALISIS PENGARUH PELAKSANAAN SUPERVISI TERHADAP KEPUASAN KERJA AUDITOR INTERNAL INSPEKTORAT SE-PROVINSI RIAU - ', Boiman; Kurnia, Pipin; Surya, Raja Adri Satriawan (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2013)
This research was conducted to determine the effect of aspects of leadership andmentoring, aspects of working conditions, and aspects of the assignment to thesatisfaction of the work of internal auditors inspectorate as Riau province. Thestudy was conducted in 13 offices spread inspectorate in Riau Province. Samplingwas carried out using non-probability sampling methods (purposive samplemethod) while the data collection techniques performed by direct methods.Processing and analysis of data using linear regression analysis with the help ofsoftware SPSS (Statistical Product and Service Solution). The test data is used formultiple linear regression is a validity test data, test reliability, and test theclassical assumptions. The results showed that the aspects of leadership andmentoring no significant effect due to the leadership and mentoring variables arevariables excluded from the backward selection method. While aspects of theworking conditions and other aspects of the assignment of a significant effect onjob satisfaction.Kata Kunci : Aspects of Leadership and Mentoring, Aspects of WorkingConditions, Aspect Assignment, Job Satisfaction.